Development of Chloroplast Genomic Resources for Oryza Species Discrimination - Song, Yun; Chen, Yan; Lv, Jizhou; Xu, Jin; Zhu, Shuifang; Li, MingFu; Chen, Naizhong (Frontiers in Plant Science, 2017)
Rice is the most important crop in the world as the staple food for over half of the population. The wild species of Oryza represent an enormous gene pool for genetic improvement of rice cultivars. Accurate and rapid identification of these species is critical for effective utilization of the wild rice germplasm. In this study, we developed valuable chloroplast molecular markers by comparing the chloroplast genomes for species identification. Four chloroplast genomes of Oryza were newly sequenced on the Illumina Hiseq platform and other fourteen Oryza species chloroplast genomes from Genbank were simultaneously taken into consideration for comparative analyses. Among eighteen Oryza chloroplast genomes, five variable regions (rps16-trnQ, trnTEYD, psbE-petL, rpoC2 and rbcL-accD) were detected for DNA barcodes, in addition to differences in simple sequence repeats (SSR) and repeat sequences. The highest species resolution (72.22%) was provided by rpoC2 and rbcL-accD with distance-based methods. Three-marker combinations (rps16-trnQ + trnTEYD + rbcL-accD, rps16-trnQ + trnTEYD + rpoC2 and rpoC2 + trnTEYD + psbE-petL) showed the best species resolution (100%). Phylogenetic analysis based on the chloroplast genome provided the best resolution of Oryza. In the comparison of chloroplast genomes in this study, identification of the most variable regions and assessment of the focal regions of divergence were efficient in developing species-specific DNA barcodes. Based on evaluation of the chloroplast genomic resources, we conclude that chloroplast genome sequences are a reliable and valuable molecular marker for exploring the wild rice genetic resource in rice improvement.